Perceived Stress, Burnout and Depression Among Pakistani Working Married Women: A Quantitative Study (Journal of Asian Development Studies, 2025)
Pakistan is a male-dominated society by culture, where women face numerous challenges in their daily lives. Recent studies have shown that working women report higher levels of perceived stress, elevated burnout, and depression. However, a gap still exists, as working married women have not yet been extensively studied concerning burnout as a mediator between perceived stress and depression. Therefore, the objective of this study is to fill that gap by investigating the association between perceived stress and depression, with burnout as a mediating variable, among 384 Pakistani working married women aged 25 to 40 with at least an intermediate level of educational qualification. The study employed a cross-sectional correlational design and utilised purposive sampling to collect data from 384 married working women in Pakistan, with a mean age of 30.54 years (SD=4.77). Three standardized questionnaires were used to assess the study variables: the Perceived Stress Scale, the Oldenburg Burnout Inventory, and the Beck Depression Inventory. Correlational analysis revealed significant relationships between perceived stress, burnout, and depression among the participants. Mediation analysis, conducted using Hayes' Process macro, indicated that burnout significantly and positively mediates the association between the predictor (perceived stress) and the outcome (depression). The study concludes with comprehensive implications, emphasizing the vital role of mental health professionals in raising awareness and encouraging women to seek psychological support.